The handbook of tunnel fire safety - Beard, Alan; Carvel, Richard (Thomas Telford, 2005)
The recent fatal fires in alpine tunnels have highlighted the necessity for tunnel fire safety installations and procedures. At present these vary from tunnel to tunnel and from country to country. This book brings together contributions from experts in all areas of tunnel fire investigation and fire fighting.